PREVALENCE OF COGNITIVE DECLINE IN PATIENTS WITH STROKE - Fatima Naseem Malik (Army Medical College Rawalpindi, 2020)
Objective: To determine the prevalence of cognitive decline among the patients of stroke and analyze the associated socio demographic factors.